2007
DOI: 10.1016/j.icarus.2006.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Comet 9P/Tempel 1 around the Deep Impact event by the OSIRIS cameras onboard Rosetta

Abstract: The OSIRIS cameras on the Rosetta spacecraft observed Comet 9P/Tempel 1 from 5 days before to 10 days after it was hit by the Deep Impact projectile. The Narrow Angle Camera (NAC) monitored the cometary dust in 5 different filters. The Wide Angle Camera (WAC) observed through filters sensitive to emissions from OH, CN, Na, and OI together with the associated continuum. Before and after the impact the comet showed regular variations in intensity. The period of the brightness changes is consistent with the rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The detection of flux from dust grains so soon after impact implies that if material from the impact traveled into the offset beam in about 10 min, the dust would have to have been moving at a speed of 700 m/s. This speed is consistent with the fastest material seen by other investigators Keller et al, 2007). The faster decrease of submicron sized amorphous carbon grain mass in the centered positions also supports the conclusion that the carbon grains are traveling at a greater speed than the amorphous olivine grains.…”
Section: Temporal Evolution Of the Dust Masssupporting
confidence: 90%
“…The detection of flux from dust grains so soon after impact implies that if material from the impact traveled into the offset beam in about 10 min, the dust would have to have been moving at a speed of 700 m/s. This speed is consistent with the fastest material seen by other investigators Keller et al, 2007). The faster decrease of submicron sized amorphous carbon grain mass in the centered positions also supports the conclusion that the carbon grains are traveling at a greater speed than the amorphous olivine grains.…”
Section: Temporal Evolution Of the Dust Masssupporting
confidence: 90%
“…Richardson et al (2007) find that the excavated mass in the DI impact ranged from 10 5 to 10 7 kg depending on the assumed strength of the surface material. However, other observations yield 4.5-9 × 10 6 kg (Keller et al, 2007) and 1.3 × 10 7 kg (Schleicher et al, 2006) for the mass of H 2 O ice released during the impact. This suggests ∼10 6 kg for a large mini-outburst.…”
Section: The Observed and Inferred Basis Of The Modelmentioning
confidence: 92%
“…It was the first reported in situ observation of a cometary outburst. Images taken by the Wide Angle Camera (WAC) of the Optical, Spectroscopic, and Infrared Remote Imaging System (OSIRIS; Keller et al 2007) on board Rosetta showed an increase of two orders of magnitude in the 67P coma surface brightness between 0940 and 1010 UT. An overview of the multi-instrument observations of the outburst can be found in Grün et al (2016).…”
Section: Introductionmentioning
confidence: 99%